(untitled) (Journal of Asian Development Studies, 2023)
This qualitative literature review evaluates the role of World Bank and International Monetary Fund (IMF) initiatives in fostering sustainable economic growth in developing countries. This research aims to critically examine existing academic literature and studies to gain comprehensive insights into the effectiveness of World Bank and IMF programs in promoting economic development in developing countries. A systematic review methodology is employed to identify and evaluate relevant scholarly articles, reports, and publications to achieve this objective. The research focuses on synthesizing the findings and key themes from these sources, exploring the methodologies and approaches used in previous studies, and evaluating the outcomes and impacts of World Bank and IMF initiatives on sustainable economic growth. The results of this study shed light on how World Bank and IMF interventions have influenced economic development in developing countries. The review highlights the key factors that contribute to the success or limitations of these programs, including policy frameworks, institutional capacity-building efforts, financial assistance mechanisms, and the integration of social and environmental sustainability considerations. The findings reveal the multifaceted nature of the World Bank and IMF’s impact on sustainable economic growth, encompassing poverty alleviation, infrastructure development, financial inclusion, governance, climate change resilience, social protection, private sector development, debt management, and human capital investment.